The importance of mini-hockey games in the u10 and u8 levels - Samuel Honório; Marco Batista; João Serrano; João Petrica; Júlio Martins; Jorge Santos (Federación Extremeña de Balonmano; University of Extremadura, 2019)
The present study aims to develop the understanding of technical-tactical situations for an effective development of the game, in this case, Hockey. Through the comparison between two situations of game: the formal game and game in (Mini-Hockey) in the "under 8" and "under 10" levels. Our objective is to verify if the reduction of field dimensions in these levels of formation, promotes a greater action in technical-tactical terms by these players, achieving a better understanding of the game. The method used was video recording of nine hockey games, five regular games and four mini-hockey games, and the data regarding of passes, shots and number of goals were recorded. We used statistical software SPSS version 20.0 where descriptive statistics, means and standard deviations, as well as non-parametric Wilcoxon and Mann-Whitney U test were used. The significance level was set at p ≤ 0.05, which allowed us to verify if there is statistical significance between the variables analyzed. In the five regular games were registered a total of 1214 passes, 229 shots and 54 goals. In the results of the mini-hockey games a total of 578 passes, 286 shots and 84 goals were recorded. With these results we may conclude that Mini-hockey promotes a greater technical-tactical action in these formation levels, with greater ball interaction, becoming an excellent teaching-learning stage for the formal 5x5 game in the field of official dimensions.